Sustainability of innovation in schools: It’s organizational foundations - López Yáñez, Julián (Profesorado, Revista de Currículum y Formación del Profesorado, 2010)
This paper reports on findings from an inquiry about the basis on which innovative schools have built and sustained changes over time. By means of case-study and ethnographic methodologies, some issues like the practice of innovation, organizational culture, informal structures of power, leadership practices and styles, and relationship patterns among internal and external educational agents, were analysed in ten primary and secondary schools in two Spanish regions. The main purpose of the inquiry was to depict the organizational knowledge about innovation achieved by the participant schools. The comprehension of this practice-based knowledge allows us to discuss some common assumptions of the theory of educational change.